SEEDS SIMILARITY OF KOCHIA SCOPARIA L. IN THE CONDITIONS OF KARAKALPAKSTAN (World Bulletin of Public Health, 2022)
In the literature, phytomeliorative works are carried out in order to improve both the natural pasture and fodder base in the desert conditions, the use of local plant resources for this purpose, and the cultivation of new plant species.The genus Kochia scoparia L. Schrad (sipse) has not been studied in our Karakalpakstan. The laboratory coagulation of the kochia we studied was 93.3%. The seeds of broom kochia (Kochia scoparia L.Schrad) germinate quickly due to their small size, they germinate 40% in 24 hours, and we found that they germinate completely in three days. According to the shelf life of seeds of Broom kochia (Kochia scoparia L. Schrad), their coagulation is 66.5 after 18 months, 80.2 after 12 months and 94.3 after 4 months. With the decrease in temperature conditions, the blueness of the seed decreases. In 2021, the blueness of kochia seed harvested was 92-94% at 250S, the blueness of kochia seed at low temperatures (+ 7 + 90) was 80- 84%, and the fat content was 10% lower. The seeds were bent in both October and December 2019. The germination differed little from each other in their lightness. Fruit bent seeds did not work. Through these studies, the left hemisphere was identified, with an average depth of planting of 0.5-1 cm
Keywords: Germinating capacity; seed germination; embryo; root